2015
DOI: 10.1186/s13041-015-0159-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor CREB3L1 mediates cAMP and glucocorticoid regulation of arginine vasopressin gene transcription in the rat hypothalamus

Abstract: BackgroundArginine vasopressin (AVP), a neuropeptide hormone that functions in the regulation of water homeostasis by controlling water re-absorption at kidneys, is synthesised in supraoptic nucleus and paraventricular nucleus of the hypothalamus. An increase in plasma osmolality stimulates secretion of AVP to blood circulation and induces AVP synthesis in these nuclei. Although studies on mechanism of AVP transcriptional regulation in hypothalamus proposed that cAMP and glucocorticoids positively and negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 52 publications
3
37
0
Order By: Relevance
“…To identify new transcriptional targets of Creb3l1, we performed RNA sequencing on our previously reported Creb3l1 knockdown AtT20 stable cell line 8 . The result showed that 5706 genes were significantly changed ( P adjusted < 0.01) in expression by Creb3l1 knockdown (see Supporting information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To identify new transcriptional targets of Creb3l1, we performed RNA sequencing on our previously reported Creb3l1 knockdown AtT20 stable cell line 8 . The result showed that 5706 genes were significantly changed ( P adjusted < 0.01) in expression by Creb3l1 knockdown (see Supporting information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Mouse pituitary cell line AtT‐20/D16v‐F2 (# 94050406; Sigma, St Louis, MO, USA) was maintained in a humidified incubator at 37°C with 5% CO 2 in Dulbecco's modified Eagle's medium (# D6546; Sigma), supplemented with 10% heat‐inactivated fetal bovine serum, 100 μg mL ‐1 penicillin/streptomycin and 2 mmol L ‐1 l ‐glutamine. Creb3l1 knockdown cell lines were established using lentivirus expressing shRNAs as described previously 8 . The sequences of all oligonucleotides and primers used in this study are provided in the Supporting information (Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RGS16 drives cAMP rhythms required for normal phasing of SCN subdomains [28]. CREB3L1 couples the core clock to Avp expression downstream of cAMP signaling [29,30]. And DUSP4 gates pERK responses to light input, likely mediating lost gating of light responses in Vip −/− mice [16,31].…”
Section: Resultsmentioning
confidence: 99%